Interchange and movements of humpback whales (Megaptera novaeangliae) between western North Pacific winter breeding grounds in northern Luzon, Philippines and Okinawa, Japan - Acebes, Jo Marie; Okabe, Haruna; Kobayashi, Nozomi; Nakagun, Shotaro; Higashi, Naoto; Uchida, Senzo (J. Cetacean Res. Manage., 2021)
Humpback whales wintering in the northern Philippines and Okinawa, Japan, belong to the western North Pacific subpopulation, now recognised as a distinct population segment. The numbers for this subpopulation are low hence it is being proposed to be listed as endangered. Although previous research revealed movements between breeding grounds, the relationship between these areas remain little understood. Recent survey efforts in the Philippines resulted in a total of 234 photo-identified individuals from 1999-2016 while Okinawa had 1,445 from 1991-2014. Within the seasons a total of 100 matches were found between the two breeding grounds including 38 males and 24 females while the rest were unknown. Within these matches, eight individuals were recorded moving within seasons, including two individuals moving across seasons multiple times. The two whales were both males, where one was recorded in both breeding grounds in three different seasons (2005, 2008 and 2012). The shortest duration of recorded sightings between grounds was one whale seen in the Philippines in late March 2012 and in Okinawa 13 days later. More females with calves were sighted in the Philippines than in Okinawa and this may indicate the Philippines as a preferred nursing ground.